PENGARUH PERAN KEPALA SEKOLAH DAN IKLIM SEKOLAH TERHADAP MUTU PENDIDIKAN PADA SEKOLAH DASAR SWASTA KECAMATAN BANYUMANIK KOTA SEMARANG - Ita Rusita; Yovitha Juliejantiningsih; Ngasbun Egar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quality education is education that successfully achieves well-defined goals, satisfies and meets expectations. The aims of this research are 1) to analyze the influence of the role of the principal on the quality of education, 2) to analyze the influence of the school climate on the quality of education, 3) to analyze the influence of the role of the principal and the school climate together on the quality of education. Quantitative research approach with survey methods. Type of correlational research. The research population was 221 teachers and the research sample was 142 teachers. Data collection with questionnaires. Data analysis techniques using descriptive data analysis, prerequisite tests which include normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The research results show that: 1) the role of the school principal influences the quality of education by 68.7%, with the regression equation Ŷ = 2.721 + 0.487 X1. with a correlation coefficient value of 0.829. 2) school climate influences the quality of education by 79.9%, with a regression equation Ŷ = 0.629 + 1.119 X2 with a correlation coefficient of 0.894. 3) the role of the principal and the school climate influence the quality of education by 80.6%, with the equation Ŷ = 3.053 + 0.106 X1 + 0.920 X2 then the correlation coefficient r is 0.898. The conclusion of this research is that the role of the principal and the school climate influence the quality of education by 80.6%. The author suggests that school principals reflect and evaluate the role of the principal and the school climate. Teachers can take part in training and seminars in order to improve school quality.